Assessing DNA methylation of ATG 5 and MAP1LC3Av1 gene in oral squamous cell carcinoma and oral leukoplakia- a cross sectional study - Nishanthi Raja; Anuradha Ganesan; Krithika Chandrasekar Lakshmi; Yesoda Aniyan (Journal of Oral Biology and Craniofacial Research)
Background: The progression and pathogenesis of oral cancer is greatly impacted by epigenetic modifications, such as DNA methylation. Autophagy, is an adaptive mechanism used to maintain the survival and integrity of cells. Oral squamous cell carcinoma is linked to a number of autophagy indicators, although it is yet unknown if DNA methylation of autophagy-related genes promotes the development of oral leukoplakia (OL), oral squamous cell carcinoma (OSCC). Aim: Our study was aimed to assess, compare and evaluate the DNA methylation of ATG5 and MAP1LC3Av1 genes in oral leukoplakia, oral squamous cell carcinoma. Materials and methods: This cross-sectional study was designed with sample size of 48 tissues which was clinically and histopathologically diagnosed as OL, OSCC and normal tissue. The samples were divided into three groups (Group A, Group B, and Group C; (n = 16 each). Following histopathological confirmation, the tissue was stored in the RNA reagent, then subjected to DNA extraction, methylation-sensitive polymerase chain reaction (MS-PCR). DNA methylation of the ATG5 and MAP1LC3Av1 genes were assessed. Results: Shapiro-Wilk and Kolmogorov-Smirnov tests showed that the values were normally distributed. Both the ATG5 and MAP1LC3Av1 genes were methylated in OSCC, OL tissues compared to normal tissues. A statistically significant results was seen among the three study groups. Conclusion: A significant difference was noted in the hypermethylation status of the promoter regions of the ATG5 and MAP1LC3Av1 genes. This provides some insight into their crucial role in the development of tumors. Future research with larger sample is needed to assess its potential clinical implications in oral carcinoma.